Pelaksanaan Wewenang Direktur Jenderal Pajak Terhadap Pengurangan dan Pembatalan Ketetapan Pajak Menurut Pasal 36 Undang-Undang Nomor 28 Tahun 2007 Tentang Ketentuan Umum dan Tata Cara Perpajakan (UU KUP) - Candra, Alexander; Sundarta, M. Imam (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
One of the potentialrevenuesof the Republic ofIndonesia's most substantialat the present timeisTax. With taxIndonesiatofinancingallactivitiessuch assubsidizingeducation, health and infrastructuredevelopmentfasisilitas, umunelection, foreigndebt, and so on. Increasedtaxrevenuesis emphasizedthe Government. TaxationLawsRulesand regulationsare stillundersupervisionby the Ministryof Justice andHuman Rights withthe operational implementationby the DirectorGeneral ofTaxationin terms of bothformal andmaterial law. For theoverseethis acceptance, it is necessary toperatuantaxlegislationis clear, unequivocaland there is nooverlapping, sowajiptaxesortaxpayers canmore obedient, anda sense ofjusticehashighaccountability. Itmay indirectlyincrease state revenueandtheauthoritytoenforce thelaw. The research method used by the authors in the discussion of this thesis, is the normative research methods, which outlines what the applicable tax law is in conformity with the norms of other formal legal. In fact in the Tax Courts in accordance with the Court of Tax Law No. 14 of 2002, still there is a trial going on in pseudo Director General of Taxes, in which decision-making is not only a clear, straightforward, and not firm. So there is still a lot of doubt on the decision. Application Process at Director General of Tax Objection still embrace the element of lack of justice, costly, time is not erratic decisions. While in the Tax Act are mentioned only 6 (six) months in the making. According to the Tax Act No. 28 of 2007, Article 36 of the Director General of Taxes may also decide to reduce, correct, cancel or eliminate penalties and interest and administration of tax assessment issued. As for the decision process of determining the tax to be paid, so the moot court in the Director General of Taxes.Courts are decided in accordance with the Tax Court Act No. 14 of 2002, is the principal authority under the power of the judiciary, can run with the principles of the judicial process, which is low cost, fast and fair. With the recent reform Tax Courts embrace principles Cheap, Fast, Simple and Fair. Description of the research that has been conducted by the author, the writer suggesting that the Implementation Authority Director General of Taxes on Tax Reduction and annulment According to Article 36 of Law No. 28 of 2007 on General Provisions and Tax Procedures should be advised eliminate.